PERTUMBUHAN DAN PRODUKSI TIGA KLON UBI KAYU GENJAH PADA TANAH ULTISOL YANG DIBERI CACAHAN BATANG SINGKONG DI LAHAN RISET PT GGP LAMPUNG TENGAH - Utomo, Setyo Dwi; Setiawan, Kukuh; Yelli, Fitri; Ardian, Ardian; Novpriansyah, Hery; Yanto, Indri; Syaifudin, Akmad; Saifulloh, Al Azizu; Noerwijati, Kartika (Universitas Lampung, 2025)
Cassava is a plant that is ranked third as a source of food in Indonesia. Apart from that, cassava is also needed in industries such as making tapioca flour. In 2021, cassava production in Lampung will be around 20-25 t/ha, this amount is still below the potential of superior cassava which reaches 35-40 t/ha. Cassava growth and production depend on the variety and land where it is cultivated. This research aims to determine the differences in growth and production of several early maturing cassava clones tested, namely Vamas-1, Vati-1, and UTK on Ultisol soil in the PT GGP research area. This research was carried out on the land of the PT GGP research division, Central Lampung, Lampung. This research was carried out from August 2022 to February 2023. The research method used was a Randomized Block Design (RAK) with one treatment, namely clones. There are 3 clones used, namely Vamas-1, Vati-1, and UTK. The experiment on each clone consisted of 3 replications with 36 plants in each replication, but 5 plants were selected from each replication as samples, so that 45 experimental units were obtained. The observation data was analyzed and then compared with the UJ5 clone data based on the Standard Deviation to determine the early maturation characteristics of the three clones. The results showed that clone treatment had no significant effect on growth and production. The number of fresh sweet potatoes at 24 weeks after planting (WAP) in terms of the quantity of clones Vamas-1, Vati-1, UTK, and UJ5 respectively was 7.3; 6.6; 6.3; and 7.3 fruit/plant with a fresh sweet potato weight of 2316,7; 2183,3; 2150,0; and 1433,3 g/plant. The starch content of Vamas-1, Vati-1, UTK, and UJ5 clones was 26,2%; 25,2%; 25,8%; and 23.2%..Keywords : early, Manihot esculenta, UTK, Vamas-1, Vati-1,